The Semiotics of Exile in Literature - Zeng, H. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
Furthering the scholarship on writers and artists as diverse as Lord Byron, Edvard Munch, Sylvia Plath, and Jorge Luis Borges, Zeng probes the semiotics of exile.  In artistic traditions the world over, exile exerts a potent and complex mythmaking power - whether it is manifest as a geographical dislocation or as a sense of cultural or psychological alienation.